2017
DOI: 10.31234/osf.io/n9kbf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lindeløv et al. (2017) Improving working memory performance in brain-injured patients using hypnotic suggestion: a randomized controlled trial

Abstract: Working memory impairment is prevalent in brain injured patients across lesion aetiologies and severities. Unfortunately, rehabilitation efforts for this impairment have hitherto yielded small- or no effects. Here we show in a randomized actively controlled trial that working memory performance can be effectively restored by suggesting to hypnotized patients that they have regained their pre-injury level of working memory functioning. Following four 1-hour sessions, 27 patients had a medium-sized improvement r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Memory. Lindeløv et al [17], using a randomized controlled trial found that hypnotic suggestions can actively restore working memory performance in patients with acquired brain injury. Kihlstrom's et al [15] pointed out that hypnosis can dissociate different forms of memory such as those of episodic and semantic memory allowing them to operate independently and accordingly with the therapeutic purposes.…”
Section: The Role Of Clinical Hypnosis In Metacognitive Knowledgementioning
confidence: 99%
“…Memory. Lindeløv et al [17], using a randomized controlled trial found that hypnotic suggestions can actively restore working memory performance in patients with acquired brain injury. Kihlstrom's et al [15] pointed out that hypnosis can dissociate different forms of memory such as those of episodic and semantic memory allowing them to operate independently and accordingly with the therapeutic purposes.…”
Section: The Role Of Clinical Hypnosis In Metacognitive Knowledgementioning
confidence: 99%